Membrane Interactome of a Recombinant Fragment of Human Surfactant Protein D Reveals GRP78 as a Novel Binding Partner in PC3, a Metastatic Prostate Cancer Cell Line - Thakur, Gargi; Sathe, Gajanan; Kundu, Indra; Biswas, Barnali; Gautam, Poonam; Alkahtani, Saad; Idicula-Thomas, Susan; Sirdeshmukh, Ravi; Kishore, Uday; Madan, Taruna (Frontiers in Immunology, 2021)
Surfactant protein-D (SP-D), a member of the collectin family has been shown to induce apoptosis in cancer cells. SP-D is composed of an N-terminal collagen-like domain and a calcium-dependent carbohydrate recognition domain (CRD). Recently, we reported that a recombinant fragment of human SP-D (rfhSP-D), composed of homotrimeric CRD region, induced intrinsic apoptotic pathway in prostate cancer cells. Here, we analyzed the membrane interactome of rfhSP-D in an androgen-independent prostate cancer cell line, PC3, by high resolution mass spectrometry and identified 347 proteins. Computational analysis of PPI network of this interactome in the context of prostate cancer metastasis and apoptosis revealed Glucose Regulated Protein of 78 kDa (GRP78) as an important binding partner of rfhSP-D. Docking studies suggested that rfhSP-D (CRD) bound to the substrate-binding domain of glycosylated GRP78. This was further supported by the observations that human recombinant GRP78 interfered with the binding of rfhSP-D to anti-SP-D polyclonal antibodies; GRP78 also significantly inhibited the binding of recombinant full-length human SP-D with a monoclonal antibody specific to the CRD in a dose-dependent manner. We conclude that the interaction with rfhSP-D is likely to interfere with the pro-survival signaling of GRP78.